MAPK8 and CAPN1 as potential biomarkers of intervertebral disc degeneration overlapping immune infiltration, autophagy, and ceRNA - Zhang, Yuxin; Zhang, Jiahui; Sun, Zhongyi; Wang, Hui; Ning, Ruonan; Xu, Longyu; Zhao, Yichen; Yang, Kai; Xi, Xiaobing; Tian, Jiwei (Frontiers in Immunology, 2023)
Background: Intervertebral disc degeneration (IDD) is one of the most common health problems in the elderly and a major causative factor in low back pain (LBP). An increasing number of studies have shown that IDD is closely associated with autophagy and immune dysregulation. Therefore, the aim of this study was to identify autophagy-related biomarkers and gene regulatory networks in IDD and to identify potential therapeutic targets. Methods: To obtain the gene expression profiles of IDD, GSE176205 and GSE167931 were downloaded from the Gene Expression Omnibus (GEO) public database. After differentially expressed genes (DEGs) analysis, KEGG, GO and GSEA enrichment were performed to explore the biological functions of DEGs. Then, differentially expressed autophagy-related genes (DE-ARGs) were crossed with the autophagy gene database. The hub genes were screened by the protein-protein interaction (PPI) network of DE-ARGs. The correlation between the hub genes and immune infiltration and the construction of the gene regulatory network of the hub genes were confirmed. Finally, qPCR was used to validate the correlation of hub genes in the rat IDD model. Results: We obtained 636 DEGs enriched in the autophagy pathway. Our analysis revealed 30 DE-ARGs, of which 6 hub genes (MAPK8, CTSB, PRKCD, SNCA, CAPN1, and EGFR) were identified using the MCODE plugin. Immune cell infiltration analysis revealed an increased proportion of CD8 T cells and M0 macrophages in IDD, while CD4 memory T cells, neutrophils, resting dendritic cells, follicular helper T cells and monocytes were much less abundant. Subsequently, the competitive endogenous RNA (ceRNA) network was constructed using 15 lncRNAs and 21 miRNAs. In qPCR validation, two hub genes, MAPK8 and CAPN1, were shown to be consistent with the bioinformatic analysis results. Conclusion: Our study identified MAPK8 and CAPN1 as key biomarkers of IDD. These key hub genes may be potential therapeutic targets for IDD.